Determinants of industrial pricing strategies in the Singapore context. - Chia, Jazzlyn Ai Li. (2009)
The purpose of this study is to examine the industrial pricing process in Singapore. Particularly, investigations were carried out on the main pricing strategies used by industrial firms and the factors that determine or influence the choice of these main pricing strategies. Additionally, the results of the local study were compared to a similar one conducted in the United States.